2002
DOI: 10.1080/09638280210124284
|View full text |Cite
|
Sign up to set email alerts
|

Return to work following vocational rehabilitation for neck, back and shoulder problems: risk factors reviewed

Abstract: A great number of demographic, psychological, social, medical, rehabilitation-related, workplace-related and benefit-system-related factors are associated with return to work. The different types of risk factor are associated in many ways. People with greater chances of job return after vocational rehabilitation are younger, native, highly educated, have a steady job and high income, are married and have stable social networks, are self-confident, happy with life, not depressed, have low level of disease sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 40 publications
1
63
0
5
Order By: Relevance
“…For employed people, it is the employer's duty to initiate this process, whereas for the unemployed it falls to the employment office. Employers have a duty to provide workplace rehabilitation, if possible; otherwise the local insurance office purchases rehabilitation measures from hospitals and private providers [11,13,14]. The primary aim of such programmes in the Swedish context is to aid the people on sick leave to restore or manage their lost working capacity and, in some cases, become independent of the welfare system [6].…”
Section: The National Policy Contextmentioning
confidence: 99%
“…For employed people, it is the employer's duty to initiate this process, whereas for the unemployed it falls to the employment office. Employers have a duty to provide workplace rehabilitation, if possible; otherwise the local insurance office purchases rehabilitation measures from hospitals and private providers [11,13,14]. The primary aim of such programmes in the Swedish context is to aid the people on sick leave to restore or manage their lost working capacity and, in some cases, become independent of the welfare system [6].…”
Section: The National Policy Contextmentioning
confidence: 99%
“…Shorter durations of professional practice were associated with the RTW in a few occupational categories, with age being a factor that could explain this amount of time. Selander et al 11 suggested that the RTW is facilitated in young people because of their better health status and motivation, in addition to their value in the labor market. The literature points to the gravity of occupational hand injuries, demonstrating that they require extended treatment and absenteeism, and result in higher levels of disability than other conditions 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that workers with a higher educational level are more likely to find other work compared to those at an educational disadvantage. An explanation for the low success rate of reinsertion of uneducated workers is that a poorer technical qualification hinders allocation in new lines of work 11 . Additionally, these workers tend to suffer more severe injuries with difficult recovery, such as amputations or crush injuries 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have found that anxiety disorders and lack of social support can deter an individual's return to work (Allen and Carlson, 2003;Larsson Lund et al, 2005). Selander et al, (2002), found that being self-confident, happy with life and not depressed were positive predictors of return to work. In addition they found that the young, native and well educated were most likely to return to work after work rehabilitation.…”
Section: Introductionmentioning
confidence: 99%